2019
DOI: 10.3889/oamjms.2019.549
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of KRAS Gene Expression and P53 Immunoexpression In Colorectal Adenocarcinoma

Abstract: BACKGROUND: Colorectal Adenocarcinoma (ADCCR) is the third most cancer not only in the world but also in Indonesia. There were 623 cases of ADCCR at Dr Hasan Sadikin hospital within 2015-2017. Both KRAS and TP53 mutation are known as genes which involve in carcinogenesis through the same pathway, namely the chromosomal instability pathway. In West Java, researches focusing on mutation KRAS and p53 also a correlation between both biomarkers among ADCCR patients are still limited. AIM: Therefore, this research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
(41 reference statements)
0
9
0
3
Order By: Relevance
“…Studies on CRC patients have found that co-mutations of both TP53 and KRAS were rare, suggesting alternate pathways for them in the development of CRC (Smith et al, 2002). Conversely, other reports detected co-existing mutations in 26 out of 140 patients (Tortola et al, 1999), and more recently 26% of 229 patients presented mutations of both KRAS and TP53 (Chow et al, 2016) and a mild correlation was observed between the expression of the KRAS gene and TP53 immunoexpression in colorectal adenocarcinoma (Rachmawati et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Studies on CRC patients have found that co-mutations of both TP53 and KRAS were rare, suggesting alternate pathways for them in the development of CRC (Smith et al, 2002). Conversely, other reports detected co-existing mutations in 26 out of 140 patients (Tortola et al, 1999), and more recently 26% of 229 patients presented mutations of both KRAS and TP53 (Chow et al, 2016) and a mild correlation was observed between the expression of the KRAS gene and TP53 immunoexpression in colorectal adenocarcinoma (Rachmawati et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Faktor risiko DM yaitu faktor yang dapat diubah (obesitas, pola hidup dan pola makan, stres) dan faktor yang tidak dapat diubah (riwayat keluarga DM usia, jenis kelamin). 2 Hiperglikemia atau peningkatan gula darah adalah efek umum dari DM yang tidak terkontrol,menyebabkan orang DM dapat mengalami perubahan atau kerusakan jangka panjang struktur dan fungsi organ tubuh lain akibat komplikasi yaitu: polineuropati, retinopati, nefropati, penyakit jantung koroner, stroke, dan penyakit arteri perifer. 3 Kasus polineuropati diabetik (PND) merupakan komplikasi terbanyak dari DM tipe 2 dengan gangguan fungsi saraf perifer yang terjadi akibat penyebab utama hiperglikemia yang diawali oleh resistensi insulin pada DM tipe 2.…”
Section: Riset Kedokteranunclassified
“…Увеличение экспрессии TP53 прямо коррелирует с увеличением пролиферативных и инвазивных признаков опухоли. Кроме того, TP53 часто сверхэкспрессируется при дисплазии эпителия крипт, вызванной язвенным колитом [36,37].…”
Section: игх маркеры колоректального ракаunclassified
“…Приобретение соматических мутаций в этом гене может снизить показатели выживаемости при лекарственно устойчивых колоректальных опухолях, которые также содержат мутации KRAS. Маркер имеет цитоплазматическое и мембранозное окрашивание [37,40].…”
Section: игх маркеры колоректального ракаunclassified